Studies on Schismatoglottideae (Araceae) of Borneo XXI — Two new species of the Schismatoglottis Calyptrata Group: Schismatoglottis heterodoxa and S. ranchanensis - Wong Sin, Yeng (BioOne Online Journals, 2012)
Two new species of the Schismatoglottis Calyptrata Group are described from Malaysian Borneo. One, S. heterodoxa, is the second rheophytic species ever recorded for the Calyptrata Group. The other, S. ranchanensis, is lithophytic, a rather rare life form for that group. A key to the Bornean rheophytic and lithophytic species of the Calyptrata Group is given and both novelties are illustrated.